Respuesta :

56 - x = 728 + 2x

-x - 2x = 728 - 56

-3x = 672

x = 672/-3

x = -224

Hope that helps. If you have any doubts plz let me know.

Answer:

56-x=728+2x

1.) rearrange

[tex]56x = 728 + 2x \\ \ - x + 56 = 728 + 2x[/tex]

[tex] - x + 56 = 728 + 2 x \\ \\ - x + 56 = 2x + 728[/tex]

2.)subtract 56 on both side

[tex] - x + 56 = 2x + 728 \\ \ - x + 56 - 56 = 2x + 728 - 56[/tex]

3.) simplify

[tex] - x = 2x + 672[/tex]

4.)Subtract 2 on both sides

[tex] - x = 2x + 672 \\ \\ - x - 2x = 2x + 672 - 2x[/tex]

5.) simplify

[tex] - x - 2x = 2x + 672 - 2x \\ \\ - 3x = 2x + 672 - 2x \\ \\ - 3x = 672[/tex]

6.)divide both sides on the same equation

[tex] - 3x = 672 \\ \\ \frac{ - 3x}{ - 3} = \frac{672}{ - 3} [/tex]

7.) simplify

[tex]x = - 224[/tex]

8.) answer

[tex]x = - 224[/tex]

if u need any help, just let me know